Developing knowledge-based leaflets and community attitudes about organic agriculture to improve students' ecological literacy - Kastawi Kastawi; Sofyan Hasanuddin Nur; Zaenal Abidin (Universitas Wiralodra, 2022)
This research aimed to produce knowledge-based leaflets and community attitudes about organic farming to improve students' ecological literacy. This research development was done based on the 4D model (Define, Design, Develop, and Disseminate) Data on community knowledge and attitudes about organic farming were obtained from questionnaires and interviews with 20 farmers. The data is implemented into leaflets. Leaflet validation was carried out by design experts, material experts, and science teachers. Limited trials to determine student responses were given to eight students. The score obtained from the validation by design experts is 49.5 or 82.5% (good). The validation results by material experts are 50.5 or 84% (good). The science teacher validation scored 45.25 or 90.5 (good). The trial by eight students obtained a percentage of 91.6% with a positive response. The results of the normalized gain score showed an increase in learning with an average score of 0.61 in the experimental class (high). The independent t-test is -4.058, at df 58, the significance value is 5%, t-table value is 2.00. Thus, it can be concluded that the leaflet developed is effective in increasing students' ecological literacy. At df 58, the significance value is 5%, and the t-table value is 2.00. Thus, it can be concluded that the leaflet developed is effective in increasing students' ecological literacy.